Restriction fragment length polymorphisms of mitochondrial DNA among five freshwater fish species of the genus Astyanax (Pisces, Characidae) - Cinthia Bachir Moysés; Lurdes F. de Almeida-Toledo (Genetics and Molecular Biology, 2002)
Restriction fragment length polymorphism (RFLP) analysis of mitochondrial DNA (mtDNA) was employed to characterize species and populations of Astyanax, a Neotropical freshwater fish genus. Samples of five species, A. altiparanae, A. fasciatus, A. lacustris, A. scabripinnis paranae and A. schubarti, from the Upper Paraná and São Francisco river basins were analyzed. Two out of the ten restriction enzymes employed generated species-specific mtDNA patterns for each of the five species. MtDNA exhibited considerable polymorphism within and among populations. All populations sampled showed relatively high values of haplotype diversity. Geographically localized haplotypes were detected for A. altiparanae and A. fasciatus from the Upper Paraná and São Francisco basins. The relationships between populations are discussed.